Preliminary studies of Volten VR4® Kaempferia parviflora herb extracts on blood glucose levels in human type-2 diabetes mellitus and its mineral element analysis - Ahmad Sabry Mohamad,; Muhammad Noor Nordin,; Ismail Che Ani,; Johan Jemberang,; Reezal Ishak,; Ahmad Najib Hasan,; Muhammad Imran Ahmad,; Roszymah Hamzah; Mohd Rahman Omar (Polish Ministry of Science and Higher Education, 2024)
Indexed by ERA